Therapeutic drug monitoring of voriconazole for treatment and prophylaxis of invasive fungal infection in children - Allegra, Sarah; Fatiguso, Giovanna; De Francia, Silvia; Favata, Fabio; Pirro, Elisa; Carcieri, Chiara; De Nicolò, Amedeo; Cusato, Jessica; Di Perri, Giovanni; D'Avolio, Antonio (British journal of clinical pharmacology, 2018)
Voriconazole therapeutic drug monitoring is not consistently recommended due to its high interpatient and intrapatient variability. Here, we aimed to describe our experience with voriconazole for treatment and prophylaxis of invasive fungal infections in paediatric patients. A fully validated high‐performance liquid chromatography–mass spectrometry method was used to quantify voriconazole concentration in plasma, at the end of dosing interval. A high interindividual variability was shown. We enrolled 237 children, 83 receiving intravenous and 154 oral voriconazole. A positive correlation between drug dose and drug plasma exposure was observed. Considering intravenous route, patients with higher serum creatinine had higher voriconazole concentrations; a positive correlation was found among drug exposure and age. Sex significantly influenced drug levels: males had higher median drug concentrations than females (P < 0.001). Close voriconazole pharmacokinetics monitoring should help individualize antifungal therapy for children.